Nutrition and your implications for endometriosis (Research, Society and Development, 2022)
Endometriosis is a disease that has several symptoms in women. Lifestyle changes, including improving eating habits with an anti-inflammatory diet, effectively contribute to mitigating symptoms. Therefore, the objective of this work is to highlight the relationship between the food profile and body composition in the development and prediction of the pathology. The study is a literature review and 38 materials were consulted for research, among them scientific articles, official, books and final paper. The research was carried out using the Scielo, PubMed and Google Scholar databases, in Portuguese, English and Spanish, published between 2011 and 2021. After reviewing the literature, the main nutrients and foods that can contribute to the reduction of symptoms or that can worsen the referred clinical condition were listed, in addition to evaluating the body composition of women with endometriosis. Food plays a fundamental role in both the development and management of endometriosis, where a pro-inflammatory food profile increases the chance of development as well as worsening symptoms, with the Nutritionist having an important contribution to improving lifestyle by providing quality of life to women with endometriosis.